A Leadless Intracardiac Transcatheter Pacing System - Reynolds, Dwight; Duray, Gabor Z; Omar, Razali; Soejima, Kyoko; Neuzil, Petr; Zhang, Shu; Narasimhan, Calambur; Steinwender, Clemens; Brugada, Josep; Lloyd, Michael; Roberts, Paul R; Sagi, Venkata; et al. (The New England journal of medicine, 2016)
BACKGROUND: A leadless intracardiac transcatheter pacing system has been designed to avoid the need for a pacemaker pocket and transvenous lead. METHODS: In a prospective multicenter study without controls, a transcatheter pacemaker was implanted in patients who had guideline-based indications for ventricular pacing. The analysis of the primary end points began when 300 patients reached 6 months of follow-up. The primary safety end point was freedom from system-related or procedure-related major complications. The primary efficacy end point was the percentage of patients with low and stable pacing capture thresholds at 6 months (≤2.0 V at a pulse width of 0.24 msec and an increase of ≤1.5 V from the time of implantation). The safety and efficacy end points were evaluated against performance goals (based on historical data) of 83% and 80%, respectively. We also performed a post hoc analysis in which the rates of major complications were compared with those in a control cohort of 2667 patients with transvenous pacemakers from six previously published studies. RESULTS: The device was successfully implanted in 719 of 725 patients (99.2%). The Kaplan-Meier estimate of the rate of the primary safety end point was 96.0% (95% confidence interval [CI], 93.9 to 97.3; P<0.001 for the comparison with the safety performance goal of 83%); there were 28 major complications in 25 of 725 patients, and no dislodgements. The rate of the primary efficacy end point was 98.3% (95% CI, 96.1 to 99.5; P<0.001 for the comparison with the efficacy performance goal of 80%) among 292 of 297 patients with paired 6-month data. Although there were 28 major complications in 25 patients, patients with transcatheter pacemakers had significantly fewer major complications than did the control patients (hazard ratio, 0.49; 95% CI, 0.33 to 0.75; P=0.001). CONCLUSIONS: In this historical comparison study, the transcatheter pacemaker met the prespecified safety and efficacy goals; it had a safety profile similar to that of a transvenous system while providing low and stable pacing thresholds. (Funded by Medtronic; Micra Transcatheter Pacing Study ClinicalTrials.gov number, NCT02004873.).
Keywords: senioři; implantované elektrody; senioři nad 80 let; design vybavení; srdeční arytmie; Pacemaker, Artificial; Kaplan-Meier Estimate; Middle Aged; mužské pohlaví; Electrodes, Implanted; Kaplanův-Meierův odhad; Prospective Studies; Adult; mladý dospělý; Arrhythmias, Cardiac; Equipment Safety; Equipment Design; Aged, 80 and over; Young Adult; ženské pohlaví; Humans; prospektivní studie; kardiostimulátor; lidé středního věku; dospělí; Female; Aged; bezpečnost vybavení; lidé; Male